Lenalidomide Enhances Immune Checkpoint Blockade Induced Immune Response in Multiple Myeloma - Görgün, Güllü Topal (Clin Cancer Res, 2015)
PURPOSE: PD1/PD-L1 signaling promotes tumor growth while inhibiting effector cell-mediated anti-tumor immune responses. Here we assessed the impact of single and dual blockade of PD1/PD-L1, alone or in combination with lenalidomide, on accessory and immune cell function as well as multiple myeloma (MM) cell growth in the BM milieu. EXPERIMENTAL DESIGN: Surface expression of PD1 on immune effector cells, and PD-L1 expression on CD138+MM cells and myeloid derived suppressor cells (MDSC) were determined on tumor cells from newly diagnosed (ND)-MM and relapsed/refractory (RR)-MM BM versus healthy donor (HD). We defined the impact of single and dual blockade of PD1/PD-L1, alone and with lenalidomide, on autologous anti-MM immune response and tumor cell growth. RESULTS: Both ND and RR patient MM cells have increased PD-L1 mRNA and surface expression compared to HD. There is also a significant increase in PD1 expression on effector cells in MM. Importantly, PD1/PD-L1-blockade abrogates BM-stroma cell (BMSC)-induced MM growth, and combined blockade of PD1/PD-L1 with lenalidomide further inhibits BMSC-induced tumor growth. These effects are associated with induction of intracellular expression of IFNγ and Granzyme-B in effector cells. Importantly, PD-L1 expression in MM is higher on MDSC than on antigen presenting cells, and PD1/PD-L1-blockade inhibits MDSC-mediated MM growth. Finally, lenalidomide with PD1/PD-L1-blockade inhibits MDSC-mediated immune suppression. CONCLUSION: Our data therefore demonstrates that checkpoint signaling plays an important role in providing the tumor-promoting, immune-suppressive microenvironment in MM, and that PD1/PD-L1-blockade induces anti-MM immune response that can be enhanced by lenalidomide, providing the framework for clinical evaluation of combination therapy.